The Role of Lipoproteins in Mycoplasma-Mediated Immunomodulation - Christodoulides, Alexei; Gupta, Neha; Yacoubian, Vahe; Maithel, Neil; Parker, Jordan; Kelesidis, Theodoros (Frontiers in Microbiology, 2018)
Mycoplasma infections, such as walking pneumonia or pelvic inflammatory diseases, are a major threat to public health. Despite their relatively small physical and genomic size, mycoplasmas are known to elicit strong host immune responses, generally inflammatory, while also being able to evade the immune system. The mycoplasma membrane is composed of approximately two-thirds protein and one-third lipid and contains several lipoproteins that are known to regulate host immune responses. Herein, the immunomodulatory effects of mycoplasma lipoproteins are reviewed. A better understanding of the immunomodulatory effects, both activating and evasive, of Mycoplasma surface lipoproteins will contribute to understanding mechanisms potentially relevant to mycoplasma disease vaccine development and treatment.